Can vertical separation of species in trawls be utilized to reduce bycatch in shrimp fisheries? - Larsen, Roger B.; Herrmann, Bent; Brcic, Jure; Sistiaga, Manu; Cerbule, Kristine; Nielsen, Kåre Nolde; Jacques, Nadine; Lomeli, Mark Joseph Max; Tokac, Adnan; Cuende, Elsa (PLOS ONE, 2021)
Several shrimp trawl fisheries use a Nordmöre sorting grid to avoid bycatch of fish. However, small fish can pass through the grid. Therefore, the retention of juvenile fish often remains an issue during shrimp trawling. We investigated the vertical distribution of deepwater shrimp ( Pandalus borealis ) and dominant bycatch species at the point where the Nordmöre grid section is installed. This was achieved using a separator frame which split the net vertically into three compartments of equal entry size. Our results showed that shrimp predominately follow the lower part of the trawl belly, whereas species such as redfish ( Sebastes spp.), cod ( Gadus morhua ), polar cod ( Boreogadus saida ) and American plaice ( Hippoglossoides platessoides ) preferred the mid-section in the aft of the trawl. Haddock ( Melanogrammus aeglefinus ) primarily entered through the upper section of the trawl belly. Using these results, we predict that a vertical separation device installed forward of a 19 mm Nordmöre grid combined with a 35 mm codend would result in a significant reduction in bycatch with only minor loss of shrimp.